KEBERLANGSUNGAN TONGKRONGAN KLASIK DI ERA GENCARAN TONGKRONGAN KEKINIAN KEC. SUMBERSARI, JEMBER - Sirah Robitha Maula; Sindi Dewi Aprillian, Sheila Agustina (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
In this increasingly modern era, everything that is touched by technology makes it easy for people to determine their lifestyle, especially among teenagers or young people, the culture of hanging out in places that are trending makes them feel happy and think they can provide entertainment for themselves. themselves and can express themselves. However, the number of contemporary hangouts or coffee shops makes classic hangouts have to continue to exist and continue to be demanded to have sustainability in the future so as not to be drowned out by the proliferation of contemporary hangouts which are more loved by most people. basic daily needs, contemporary hangouts provide more adequate facilities such as Wi-Fi, live music, and interior designs that are aesthetic and instagramable. This paper aims to find out how classic hangouts are sustainable amidst the proliferation of contemporary hangouts. The method used in this study is a phenomenological approach by collecting interview data, observation, and documentation. The presence of a contemporary hangout or coffee shop makes a classic hangout have to rack its brains in order to balance its existence in the midst of a contemporary hangout. The majority of classic tongkrongan owners have principles that they believe in, namely the principles of work culture which contain certain values, both in the form of hard work, enthusiasm for work, and being grateful for the process of the business being undertaken